Tapping the Markets: Opportunities for Domestic Investments in Water and Sanitation for the Poor - Sy, Jemima (World Bank, 2015)
What needs to be done to enable the domestic private sector to expand its role in the provision of safe water and improved sanitation to the poor in developing countries? Is an expanded role constrained because there is limited market potential, or is the problem the fact that business models cannot support an expansion of supply? Are government policies and the investment climate making expansion too costly or risky for enterprises to scale up their operations? This book presents the results of a detailed examination of market opportunities for the domestic private sector in the provision of piped water and on-site sanitation services in rural and semi-urban areas and of the commercial, policy, and investment climate that affect the response to these opportunities. It is based on case studies conducted in Bangladesh, Benin, Cambodia, Indonesia, Peru, and Tanzania. The results of focus group discussions with poor households, surveys of enterprises directly serving poor households, and analysis of the supply chains that support them provide insights into the nature of demand for services, the prevailing business models adopted by enterprises, and the impact of policy on decisions to invest or expand operations. The issues preventing the large market for providing poor—and nonpoor—households with piped water and on-site sanitation differ in important ways. This book therefore addresses the two sectors separately. The first part of the book analyzes the challenges facing domestic providers of piped water in Bangladesh, Benin, and Cambodia, countries where very different models of private provision have emerged in response to differing approaches taken by government. The second part analyzes providers of on-site sanitation services in Bangladesh, Indonesia, Peru, and Tanzania, where the models are similar and all providers face demand- and supply-side challenges that are largely unaffected by government policy. This book will be of interest to governments and their multilateral and bilateral development partners, as well as local and international nongovernment agencies concerned with reducing the heavy toll that lack of access to safe water and hygienic sanitation is imposing on poor people around the world. It proposes recommendations that each of these actors can adopt to harness the entrepreneurial capabilities of the domestic private sector to address this continuing challenge.